Teaching English Grammar through Animated Movies - HAMMAD MUSHTAQ; TASKEEN ZEHRA (NUST Journal of Social Sciences and Humanities, 2021)
This study seeks to examine how various components of English grammar can be taught through animated movies. The study demonstrates the use of gerunds in a sentence or a discourse through an animated feature film Tangled. The data for this research was taken from the students of grade eight. The students were shown various video clips, comprising dialogues and songs, from the movie and asked to identify the use of gerunds. Later, the students were given various worksheets containing tasks, based on the use of gerunds in a sentence. The students remained very responsive during the whole lesson and effectively learned the use of gerunds and the difference between gerunds and the present participle. The study concluded that animated movies in grammar teaching classes can serve as a positive reinforcement tool for the language learning process as the animated movies considerably increase the learning speed and proficiency of the students.